2021
DOI: 10.3390/ijms22115719
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Signaling in the Pathophysiology of Alzheimer’s Disease: Beneficial Effects of Flavonoids for Neuroprotection

Abstract: The function of the brain-derived neurotrophic factor (BDNF) via activation through its high-affinity receptor Tropomyosin receptor kinase B (TrkB) has a pivotal role in cell differentiation, cell survival, synaptic plasticity, and both embryonic and adult neurogenesis in central nervous system neurons. A number of studies have demonstrated the possible involvement of altered expression and action of the BDNF/TrkB signaling in the pathogenesis of neurodegenerative diseases, including Alzheimer’s disease (AD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…76 These results suggest that the relationship between mean change in DHA levels (ΔDHA) and serum BDNF after 12 months of intervention trials contributed to the cognitive improvements observed. BDNF-induced increases in neural spine density, synaptogenesis, and thereby synaptic function, 77,78 and could potentially account for the improvement of cognitive scores after prolonged intake of ADPP. However, why PO alone had no impact on serum BDNF levels in remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…76 These results suggest that the relationship between mean change in DHA levels (ΔDHA) and serum BDNF after 12 months of intervention trials contributed to the cognitive improvements observed. BDNF-induced increases in neural spine density, synaptogenesis, and thereby synaptic function, 77,78 and could potentially account for the improvement of cognitive scores after prolonged intake of ADPP. However, why PO alone had no impact on serum BDNF levels in remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…We have employed only selected conventional EEG parameters that have shown in previous studies reliable test-retest reliability ( Gudmundsson et al, 2007 ; Näpflin et al, 2007 ) at the individual level, which was important for the present study with the limited number of patients. Since the molecular family of NGFs plays an important role in synaptic plasticity ( Liu et al, 2014 ; Numakawa and Odaka, 2021 ) it would be of interest to further explore on a larger sample size EEG connectivity measures that are more closely related to the efficacy of neuronal networks.…”
Section: Discussionmentioning
confidence: 99%
“…The major hallmarks of AD are the increase in amyloid-β precursor protein (APP), the deposition of amyloid-β (Aβ) plaques and α-synuclein (α-Syn), the activation of astrocytes/microglia, the hyperphosphorylation and aggregation of tau, neuroinflammation and the cell death of neurons [81][82][83]. BDNF/TrkB neurotrophic signaling contributes to neuronal survival, development, and synaptic plasticity, and dysregulation of the BDNF/TrkB signaling pathway underlies neurodegeneration in AD [84,85]. It has been reported that ROS elevation causes oxidative stress, the dysfunction of astrocytes, the promotion of Aβ generation, neuronal damage, cognitive decline, and dementia in AD [86,87].…”
Section: Microglia In Alzheimer's Disease (Ad)mentioning
confidence: 99%